PEMANFAATAN KULIT JAGUNG (Zea mays) UNTUK PRODUKSI GLUKOSA MENGGUNAKAN KAPANG Trichoderma sp. - Saiful Safari; Syaiful Bahri; Nurhaeni Nurhaeni (KOVALEN: Jurnal Riset Kimia, 2017)
This study uses corn husk for the production of glucose by fermentation with the fungus Trichoderma sp. The aim is to determine the amount of Trichoderma sp. which is the best to produce the highest glucose with a variety of heavy fungus are 6, 9, and 12 grams in 25 grams of flour corn husk. Fermentation time variation  3, 4, and 5 weeks. Determination of the glucose level with DNS method using UV-Vis spectrophotometry. The study design using RAL factorial consisting of two factors, namely the weight of the fungus and fermentation time, each factor consists of 3 levels and is done in duplicate.The results showed that high glucose levels obtained in the addition of 12 grams of fungus and fermentation time 4 weeks with a glucose level of 21.72%.Keywords: Corn husk, Trichoderma weight, Time of fermentation, Glucose